Evaluation of raw ulva lactuca meal as a bioactive feed supplement to enhance the expression of growth-promoting and immunological genes of the pacific white shrimp, Penaeus vannamei. - Dinaga, Chris Ian P. (2023)
Penaeus vannamei is a globally important farmed shrimp and efforts for the discovery and development of dietary feed additives to optimize growth and improve disease resistance has received significant attention recently. In this regard, a 60-day feeding trial was conducted to evaluate the influence of raw Ulva lactuca meal supplementation on the growth and expression of immunological and growth-related genes of P. vannamei. Five experimental diets containing 0.5 (UM0.5), 1% (UM1.0), 2.5 (UM2.5), 5.0 (UM5.0), and 10% (UM10.0) raw Ulva meal, and a control diet, with no inclusions, were evaluated in the present study. Results showed that the UM0.5 diet significantly improved the weight gain (%WG) and specific growth rate (SGR) of P. vannamei as compared to the control group. No significant difference was also observed in the survival rate of shrimp in all treatments, as well as the feed conversion ratio (FCR). results also indicate that the growth promoting effects of 0.5% Ulva inclusion is associated with upregulation in the expression of muscle growth-promoting genes including α-actin, tor, 4e-bp, myosin heavy chain (MHC) and s6k, relative to the control group. Expression of immune related genes including crustin and penaeidin were also upregulated in the UM0.5 treated group as compated to the control. Collectively, U. lactuca supplementation at 0.5% could be a practical strategy to improve growth, productivity and improve immunological response of cultures P. vannamei.
Thesis (Undergraduate, Bachelor of Science in Fisheries)Institute of Aquaculture, College of Fisheries and Ocean Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2023.
Keywords: Shrimp; Penaeus Vannamei